Ma'na Cum Maghza as Sahiron Syamsuddin's Approach to the Science of the Qur'an and Tafsir - Sa'dina, Ahmad Midrar; Muhammad, Farhan (Jurnal Iman dan Spiritualitas, 2025)
The relevance of how the Al-Qur’an is interpreted in the modern day is explicitly covered in this essay. This approach’s primary goal is to investigate the meaning and historical relevance of the verses under interpretation and then transform that historical significance into dynamic significance. The following procedures are used to determine historical meaning and significance: (a) textual analysis, (b) intratextuality, (c) intertextuality, (d) examination of the historical setting in which the verse was revealed, and (e) reconstruction of the verse’s major meaning. To determine the verse’s dynamic significance, the following procedures are followed: (a) classifying the verse, (b) contextualizing and re-actualizing the verse’s significance, (c) identifying the verse’s symbolic meaning, and (d) fortifying the verse’s construction with knowledge to assist others. It is impossible to divorce the research methodology employed in this study from the realization of the ma’na-cum-maghza approach’s urgency. Because content analysis is used in this study, Sahiron’s work in applying the ma’na-cum-maghza methodology to QS Al-Maidah (5): 51 may be thoroughly examined. Similarly, the qualitative method used in this study can interpret ma’na-cum-maghza in the context of today, particularly in light of modern interpretations, which are supported by information the author gathered from books, documents, journals, and notes. Some observations about Ma’na-cum-Maghza. The author explains the connecting bridge as an explanation of ma’na-cum-maghza by utilizing source triangulation to find the validity of the data and sample Q 5:51, which Sahiron interpreted. This produces research that is compatible with the disclosure of the urgency of ma’na-cum-maghza.